Pengaruh Variasi Metode Ekstraksi Terhadap Perolehan Senyawa Antioksidan Pada Daun Katuk (Sauropus androgynus (L.) Merr) - Hikmawanti, Ni Putu Ermi; Fatmawati, Sofia; Arifin, Zainal; ., Vindianita (Jurnal Farmasi Udayana; Vol. 10, No 1, Tahun 2021, 2021)
S. androgynus (Phyllanthaceae) contains natural antioxidant compounds such as phenolics and flavonoid derivatives. The successful to obtain the plant metabolite compounds depends on the extraction method. This study aims to determine the total phenolics and flavonoids content of the ethanolic extract of S. androgynus leaves obtained from three types of extraction methods, namely maceration, Soxhletation, and ultrasonic. Determination of total phenolics and flavonoids content was carried out by colorimetric method using Folin-ciocalteu and AlCl 3 10% reagents, respectively. The absorbance of the reaction was measured using a UV-Vis spectrophotometer. Total phenolics content is expressed as equivalent to gallic acid, while total flavonoid content is expressed as equivalent to quercetin. Determination of the extract's antioxidant activity was carried out against DPPH free radical and expressed by the IC 50 (ppm) value. The results showed that the ultrasonic extraction method produced the best levels of phenolics (42.96 ± 0.51 mgGAE/g), flavonoids (12.05 ± 0.36 mgQE/g) and antioxidant activity (IC 50 = 81.43 ± 2.63 ppm) in ethanolic extract of S. androgynus leaves compared to another extraction method (maceration > Soxhletation). Thus, it can be concluded that the ultrasonic extraction method is an efficient and effective extraction method to produce high antioxidant compounds in ethanolic extract of S. androgynus leaves.